Challenges faced by teachers on mediating the play of children with special educational needs in early childhood education - Moraes Sant'anna, Maria Madalena; Manzini, Eduardo José [UNESP]; Ramos Vosgerau, Dilmeire Sant'anna; Messias Fialho Capellini, Vera Lúcia [UNESP]; Pfeifer, Luzia Iara (University of Minho, 2018)
The National Education Standards for Early Childhood prioritize skills development of children up to five years old, taking play as a guideline of learning. The objective of this study was to identify the perceptions of teachers on the difficulties to perform and mediate the play of children with special educational needs (SEN) in early childhood education. It is a qualitative research, which collected data using interviews with 31 teachers of 11 children in seven Early Childhood Education centers, in Paraná state town. The interviews were analysed using content analysis procedures that revealed two main themes: mediation and difficulties. The results indicated that teachers play more with these children when there are two teachers in the room; they demonstrated difficulties in mediation when playing with children with pervasive developmental disorders and intellectual disabilities, which does not happen with children with physical disabilities. There is a need of greater interaction with health professionals, more individualized perception of children with special educational needs, and greater investment in in-service teacher training, mainly in what comes to knowing strategies to mediate play.
Les défis des enseignants dans la médiation des jeux des enfants aux besoins éducatifs spéciaux dans l´éducation de enfants
Desafiosdosprofessoresnamediaçãodasbrincadeiras de crianças com necessidades educacionais especiais na educação infantil
Keywords: Early childhood education; In-service teacher training programs; Key-words: Playing; Special educational needs